Budaya dan Komunikasi Kesehatan (Studi Pandangan Kesehatan pada Masyarakat Sunda dalam Tradisi Makan Lalapan) - Retno Hendariningrum (LUGAS Jurnal Komunikasi, 2018)
Culture is communication and communication is culture. Humans learn culture through communication. At the same time communication is a reflection of human culture. Culture is a subjective and objective element created by humans that increased survival of life and resulted in the satisfaction of actors in ecological niches. Cultures are spread among those who can communicate with each other because they have the same language and live at the same time and place. Culture can be learned, passed down from generation to generation. Culture can be learned through fairy tales, legends and myths. It is similar in a view of Sundanese public health on the tradition of eating fresh vegetables. This study aims to describe the public health view of Sundanese in the tradition of eating fresh vegetables. The research method used qualitative approach. Technique of collecting data was done by interview process and literature study. This study was conducted in Sumedang area of West Java. The results show that the healthy view in the tradition of eating fresh vegetables in Sundanese society is passed down from generation to generation and obtained through informal learning process, formal learning, fairy tales, and myths.